Pregunta
upstudy study bank question image url

3. Definition of the Derivative (part 2) For problems (a)-(d) below, \( a, b \) and \( c \) are constant. (a) Use the definition of the derivative to show that the derivative of the parabola \( f(x)= \) \( a x^{2}-b x+c \) is \( f^{\prime}(x)=2 a x-b \). (b) Use the definition of the derivative to show that the derivative of a cubic function \( f(x)=a x^{3} \) is \( f^{\prime}(x)=3 a x^{2} \). (c) Use the definition of the derivative to show that the derivative of the function \( f(x)=\sqrt{a x} \) is \( f^{\prime}(x)=\frac{a}{2 \sqrt{a x}} \). (d) Use the definition of the derivative to show that the derivative of the function \( f(x)=\frac{a}{b x} \) is \( f^{\prime}(x)=-\frac{a}{b x^{2}} \). (e) Verify your solutions to (a)-(d) using the Derivative Rules (Power Rule, Constant Multiple Rule, etc.).

Ask by Chan Long. in the United States
Feb 18,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

(a) The derivative of \( f(x) = a x^{2} - b x + c \) is \( f^{\prime}(x) = 2 a x - b \). (b) The derivative of \( f(x) = a x^{3} \) is \( f^{\prime}(x) = 3 a x^{2} \). (c) The derivative of \( f(x) = \sqrt{a x} \) is \( f^{\prime}(x) = \frac{a}{2 \sqrt{a x}} \). (d) The derivative of \( f(x) = \frac{a}{b x} \) is \( f^{\prime}(x) = -\frac{a}{b x^{2}} \). (e) The solutions from parts (a)-(d) are verified using the Power Rule, Constant Multiple Rule, and Chain Rule.

Solución

We are going to use the definition   f′(x) = limₕ→0 [f(x + h) − f(x)]/h to differentiate each function. Finally, we’ll verify our answers using the standard derivative rules. ───────────────────────────── (a) f(x) = ax² – bx + c Step 1. Write f(x + h):   f(x + h) = a(x + h)² – b(x + h) + c Step 2. Expand:   a(x + h)² = a(x² + 2xh + h²) = ax² + 2axh + ah²   – b(x + h) = –bx – bh Thus, f(x + h) = ax² + 2axh + ah² – bx – bh + c Step 3. Compute the difference:   f(x + h) – f(x) = [ax² + 2axh + ah² – bx – bh + c] – [ax² – bx + c]     = 2axh + ah² – bh Step 4. Form the difference quotient:   [f(x + h) − f(x)]/h = (2axh + ah² – bh)/h     = 2ax + ah – b   (for h ≠ 0) Step 5. Take the limit as h → 0:   f′(x) = limₕ→0 [2ax + ah – b] = 2ax – b ───────────────────────────── (b) f(x) = ax³ Step 1. Write f(x + h):   f(x + h) = a(x + h)³ Step 2. Expand (x + h)³:   (x + h)³ = x³ + 3x²h + 3xh² + h³ Thus, f(x + h) = a(x³ + 3x²h + 3xh² + h³) = ax³ + 3ax²h + 3axh² + ah³ Step 3. Difference:   f(x + h) – f(x) = [ax³ + 3ax²h + 3axh² + ah³] – ax³ = 3ax²h + 3axh² + ah³ Step 4. Difference quotient:   [f(x + h) − f(x)]/h = (3ax²h + 3axh² + ah³)/h     = 3ax² + 3axh + ah² Step 5. Let h → 0:   f′(x) = limₕ→0 [3ax² + 3axh + ah²] = 3ax² ───────────────────────────── (c) f(x) = √(ax)    or   (ax)^(1/2) Step 1. Write f(x + h):   f(x + h) = √(a(x + h)) = √(ax + ah) Step 2. Form the difference quotient:   [f(x + h) − f(x)]/h = [√(ax + ah) − √(ax)] / h Step 3. Multiply by the conjugate over itself to simplify:   = { [√(ax + ah) − √(ax)] · [√(ax + ah) + √(ax)] } / { h [√(ax + ah) + √(ax)] }   The numerator becomes:    (ax + ah) – ax = ah Thus, the expression simplifies to:   = [ah] / [h (√(ax + ah) + √(ax))]   Cancel h (assuming h ≠ 0):   = a / [√(ax + ah) + √(ax)] Step 4. Take the limit as h → 0:   As h → 0, √(ax + ah) → √(ax).   Thus, limit becomes:   f′(x) = a / [2√(ax)]   or   f′(x) = a/(2√(ax)) ───────────────────────────── (d) f(x) = a/(bx)    which can also be written as  (a/b)(1/x) Step 1. Write f(x + h):   f(x + h) = a/(b(x + h)) Step 2. Form the difference quotient:   [f(x + h) − f(x)]/h = [a/(b(x + h)) − a/(bx)] / h Step 3. Combine the two fractions:   Find a common denominator for the terms in brackets:   Common denominator = b x(x + h)   Thus, a/(b(x + h)) − a/(bx) = [a x – a(x + h)] / [b x(x + h)]     = [a x – a x – a h] / [b x(x + h)] = (–a h) / [b x(x + h)] Step 4. Divide by h:   [f(x + h) − f(x)]/h = (–a h) / [b x(x + h) · h] = –a / [b x(x + h)] Step 5. Take the limit as h → 0:   As h → 0, (x + h) → x, so   f′(x) = –a / [b x²] ───────────────────────────── (e) Verification Using Derivative Rules Let’s quickly check each result with known rules: 1. For (a) f(x) = ax² – bx + c, using the power rule and constant multiple rule:   d/dx(ax²) = 2ax, d/dx(–bx) = –b, d/dx(c) = 0   Thus, f′(x) = 2ax – b. 2. For (b) f(x) = ax³:   d/dx(ax³) = a · 3x² = 3ax². 3. For (c) f(x) = (ax)^(1/2):   Using the chain rule: d/dx [ (ax)^(1/2) ] = (1/2)(ax)^(–1/2) · a = a/(2√(ax)). 4. For (d) f(x) = a/(bx) = (a/b)x^(–1):   d/dx[(a/b)x^(–1)] = (a/b)(–1)x^(–2) = –a/(b x²). ───────────────────────────── Summary of Answers: (a) f′(x) = 2ax – b (b) f′(x) = 3ax² (c) f′(x) = a/(2√(ax)) (d) f′(x) = –a/(b x²) All our results match the verification using the derivative rules.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To really appreciate the magic of derivatives, let’s travel back to the late 17th century when Sir Isaac Newton and Gottfried Wilhelm Leibniz independently developed calculus. This was a revolutionary time in mathematics! Their work laid the groundwork for not just derivatives but also integral calculus, dramatically transforming both science and engineering. Their notations, such as \( f'(x) \) for derivatives, are still in playful use today! Now, how do these derivatives make a splash in the real world? Think about a car's speedometer—it measures how fast your car is going at any given moment. Mathematically speaking, the speed of the car is like the derivative of the function that describes its position over time. In a nutshell, derivatives help us understand change, making them handy in physics, economics, biology, and beyond!

preguntas relacionadas

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad